Pengaruh Financial Technology Peer to Peer Lending dan Uang Elektronik (E-Money) terhadap Pertumbuhan Ekonomi di Indonesia (Tahun 2021-2023) - Septiani, Sista; Lalita, Salma Farah; Zahra, Dila Regita (STIE Indonesia Banking School, 2024)
Rapid technological developments in the last few decades have had a major impact on the financial services industry. On the other hand, technological developments have given rise to new innovations such as peer to peer lending and digital payments. These two types of fintech are currently popular financial services. The existence of these two types helps people in the Covid-19 conditions because relying on technology, all transaction activities can be carried out. This research aims to determine the influence of fintech peer to peer lending and digital electronic money payments simultaneously on economic growth in Indonesia and to determine the influence of fintech peer to peer lending and digital electronic money payments partially on economic growth in Indonesia. The data used in this research is secondary data for 2021-2023. The analysis used is multiple linear regression analysis. The analytical tool used to carry out the analysis is stata 17. The results of the research show that the fintech peer to peer lending variable has a positive and significant effect on Economic Growth in Indonesia, the electronic money (E-Money) variable has a positive and significant effect on Economic Growth in Indonesia, and Simultaneously, the variables of fintech peer to peer lending and digital electronic money payments influence economic growth in Indonesia.